"Needing different things from different people" – a qualitative exploration of recovery in first episode psychosis. Issue 1 (2nd January 2020) - Hansen, Hege; Stige, Signe Hjelen; Davidson, Larry; Løberg, Else-Marie; Veseth, Marius
ABSTRACT: Social factors seem to play an important role in people's recovery processes, yet little attention has been given to such aspects in relation to early psychosis. In this study, we explored how young adults with first episode psychosis experienced relationships inside and outside the mental healthcare services related to their early recovery processes. We interviewed ten young adults who had been in contact with an early detection team for psychosis. The analysis involved thematic and reflexive team-based methods and drew on hermeneutic–phenomenological perspectives. We identified two themes concerning relationships with professionals: 1) being seen as a unique person with preferences and 2) getting help when you are lost. We came across three additional themes, this time, in relation to family and friends: 3) supportive family networks, 4) they cannot understand everything, and 5) different kinds of friendships. Our findings revealed that people both within and outside mental healthcare services were seen as essential (for better or worse) and often played complementary roles.